Bride Trafficking in Southeast Asia: Understanding the Socioeconomic, Legal, and Human Rights - Putri Aulia, Yolanda; Teguh Santoso, Made Panji (Interdependence Journal of International Studies, 2024)
Bride trafficking in Southeast Asia is a complex issue influenced by socioeconomic factors such as poverty, gender inequality, and disparities in education and employment. Globalisation, migration, and social pressures also contribute to the increasing cases. Legal aspects are crucial to understanding and addressing this issue. This research examines the existing legal frameworks in Southeast Asian member countries, including regulations on human trafficking, victim protection, and law enforcement. It reviews the psychological, physical, and social impacts of victims and emphasises the need for protection, rehabilitation, and access to justice. The research methodology is qualitative with a descriptive approach, based on a literature review and expert responses. The article also highlights the role of ASEAN in addressing this issue, highlighting its potential to facilitate cooperation among member countries. This comprehensive understanding of the phenomenon is expected to serve as a foundation for ongoing efforts to combat bride trafficking and protect human rights in the region